An investigation of physical activity level, sedentary time and bone mineral density in relation to sclerostin level in postmenopausal women with type 2 diabetes mellitus - Othman, Mazra (2025)
People with type 2 diabetes (T2D) have been associated with an increased risk of fractures at any skeletal site due to the poorer quality of the bone, despite having greater bone mineral density when compared to osteoporotic and normal non-T2D people. Studies showed that postmenopausal women with fragility fractures have high sclerostin levels compared to those without fractures, while physical activities (PA) were inversely related to sclerostin levels. In this study, different levels of PA (sedentary, moderate, vigorous PA and MVPA) levels were objectively measured to assess their influence on sclerostin levels in T2D postmenopausal women. This cross-sectional study involved 71 postmenopausal T2D women, aged 59.5±4.1 years from the Diabetic Clinic, Hospital Pakar Universiti Sains Malaysia. Health history of postmenopausal and T2D duration, also other chronic diseases were obtained, followed by calcium intake (mg/day) using a validated food frequency questionnaire. Anthropometry measurements were recorded and fasting blood glucose (mmol/L), HbA1c (%) and sclerostin (pmol/L) were obtained via blood assay. Using dual-energy X-ray absorptiometry (DEXA), bone mineral density (BMD, kg/cm2), T-score (SD), body fat (%), total lean mass (%), and appendicular lean mass index (ALMI, kg/m2) were derived. Participants wore an accelerometer for a week during waking hours where those with a minimum of 10-h wear/day and for a minimum of four days of valid data were analysed. Accelerometer data were analysed using the GGIR package for R-software. Using SPSS version 27, descriptive output, correlation and multivariable regression analyses and outcomes were obtained. Overall, eight women (11%) were newly identified as having osteoporosis with average T-scores -3.3±0.6 SD. From our correlation analysis, duration of T2D, years (r = 0.50), ALMI, kg/m2 (r = 0.14) and average MVPA, min/day (r = -0.4) were significantly related to sclerostin levels (p<0.05). Sedentary (339.3±83.6 min/day), light (205.2±37.1 min/day), moderate (32.0±17.2 min/day) and vigorous PA (0.4±0.9min/day) were not correlated to sclerostin levels. The multivariable regression model predicted as much as 33% (F = 5.63, p<0.003) of sclerostin outcomes are influenced by the duration of T2D diagnosed (β= 1.070, p=0.009) and MVPA (β = -0.292, p = 0.056) while controlling for appendicular ALMI, kg/m2 (β= -0.010, p= 0.990). In conclusion, the duration of diagnosed T2D influenced the sclerostin levels, which may impair bone formation while accounting for appendicular muscle. More in-depth investigations are needed to understand these results of possible MVPA influence on sclerostin in T2D postmenopausal women.